Schnabel, Eckhard J., Jesus in Jerusalem. The Last Days. - Rafael Sanz Valdivieso (Carthaginensia, 2020)
Es recensión de Schnabel, Eckhard J., Jesus in Jerusalem. The Last Days. Foreword by Craig A. Evan. William B. Eerdmans Publishing Company, Grand Rapids, Michigan, 2018.